ANALISIS TEKS DAN KONTEKS TEKS DRAMA KARYA SISWA SEKOLAH MENENGAH ATAS - Hari Agus Sasongko; Nugraheni Eko Wardani; Raheni Suhita (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to determine the textual and contextual aspects of the drama text by the class XI SMA Negeri 1 Sukoharjo school year 2016-2017. The research used in this study is analysis of the content analyses with a qualitative approach. The primary Data used in this study was a collection of drama text by the XI SMA Negeri 1 Sukoharjo class. The secondary Data used is the form of articles, books, journals and research results conducted by some researchers. The Data used is taken by the purposive sampling method. To test the validity/validity of data in this study using the source triangulation techniques, and triangulation theory. The results of the study were 179 reference data, 23 60 data for the The researchers found three reference data, i.e. persona, demonstrative, and comparative references. The details are as follows: There are 122 data-refering personas, 41 demonstration reference data, and 16 comparative refering. In the drama text by the class XI SMA Negeri 1 Sukoharjo also found a lexical aspect. The lexical aspects found are: (1) Reps, (2) Sinonimi, (3) Antonimi, and (4) collocations. Details are as follows: 37 data reps, 6 data Sinonimi, 12 data Antonimi, and 16 colocation data. In this study there were four principles that became a reference in the contextual analysis of the drama text, namely: 1) The principle of personal interpretation, 2) The principle of locational interpretation, 3) The principle of temporal interpretation, and 4) the principle of analogy. Based on this, it can be noted that there is a conjugual element in the collection of drama text by the students of the class XI SMA Negeri 1 Sukoharjo. The manuscript of a drama text by SMA Negeri 1 Sukoharjo is a textual aspect, lexical and grammatically. There are four principles that are referenced in the contextual analysis of the drama text, i.e. personal interpretation principles, locational interpretation principles, temporal interpretation principles, and analogy principles.